Quantitative methods - Odyssey Productions LLC; Insight Media (firm) ([New York] : Distributed by Insight Media, 2006)
This DVD on quantitative research methods in the social sciences is broken down into 6 segments. The video discusses how social scientists study how and why people do what they do by looking at cause, effect and mitigating factors that relate to cause and effect. Experts explain this and how governments, advertising agencies and social scientists both conduct and use these studies
Questions of quantitative research -- Principles of measurement -- Experiments -- Surveys -- Application -- Conclusions
Title from title screen
Keywords: Quantitative research; Social sciences -- Research -- Methodology; Social sciences -- Statistical methods